Injustices of Shadow Information Technology in Creating Open Educational Resources - Mncube, Siphamandla; Legodi, Alex; Langa, Nozuko Precious (Journal of Educational Science and Technology (EST), 2024)
The emergence of open educational resources (OER) promotes open access which aims to widen information access as part of smart learning in higher education institutions. However, this has caused these institutions to rely on shadow information technology (SIT) for information access and service delivery, to the point where shadow IT principles contradict open education principles. When adopting and developing OER, academics, developers, and students often opt for different software or system software based on the usability and preferences of the system. Higher education institutions (HEIs), such as the University of South Africa (UNISA), are still conscious of the IT policy in terms of the appropriation of prescribed information and communication technology (ICT). However, this institution advocates for the adoption and development of OER, and social injustices when appropriating shadow IT are not yet addressed. To investigate the challenges and injustices encountered by academics in the utilization of shadow IT when creating OER, this study opted for a qualitative research approach. The data source was academics responsible for tuition and research. For data triangulation purposes, documents such as ICT policy, tuition policy, and comprehensive open distance e-learning (CODeL) policy were considered. To propose a model, this study utilized various concepts from different theories such as "structure", which refers to the rules and resources that actors rely on in their practice and form the systems' pattern; the "used technology", which describes how user groups utilize existing technology; and the negative impacts of shadow IT (cost, risk, inconsistency, and control). The study established that, while creating OER, academics rely primarily on shadow IT which has negative impacts in an organization. This is an indication of academic stakeholders continuing to break the shadow IT roles, consciously or unsuspectingly, by being innovative while complying with the institutional mandate of open access in education. In addition to the suggestion of a shadow IT injustices model as the main contribution, this study further proposed that the institutional social capital needs to articulate social injustices associated with shadow IT to protect academics during the creation of OER. This implies that future research may examine the shadow IT injustices among all other twenty-six public universities in South Africa.